2015
DOI: 10.1210/me.2014-1335
|View full text |Cite
|
Sign up to set email alerts
|

Induction of miR-132 and miR-212 Expression by Glucagon-Like Peptide 1 (GLP-1) in Rodent and Human Pancreatic β-Cells

Abstract: Better understanding how glucagon-like peptide 1 (GLP-1) promotes pancreatic β-cell function and/or mass may uncover new treatment for type 2 diabetes. In this study, we investigated the potential involvement of microRNAs (miRNAs) in the effect of GLP-1 on glucose-stimulated insulin secretion. miRNA levels in INS-1 cells and isolated rodent and human islets treated with GLP-1 in vitro and in vivo (with osmotic pumps) were measured by real-time quantitative PCR. The role of miRNAs on insulin secretion was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…In that study our group showed putative transcription factor binding sites for Calmodulin Binding Transcription Activator 1 (Camta1) and NK2 homeobox protein, Nkx2-2. Elsewhere, we and others also demonstrated cAMP-dependent regulation of the miR-132/212 cluster through a PKA-dependent mechanism35 involving cAMP-response element (CRE)-binding proteins and CRTC136. In db / db and high-fat diet fed mice, miR-132 and miR-184 in the pancreatic islets were suggested to be induced by hyperglycaemic and hyperlipidaemic conditions typically encountered in prediabetic and diabetic states37.…”
Section: Discussionmentioning
confidence: 69%
“…In that study our group showed putative transcription factor binding sites for Calmodulin Binding Transcription Activator 1 (Camta1) and NK2 homeobox protein, Nkx2-2. Elsewhere, we and others also demonstrated cAMP-dependent regulation of the miR-132/212 cluster through a PKA-dependent mechanism35 involving cAMP-response element (CRE)-binding proteins and CRTC136. In db / db and high-fat diet fed mice, miR-132 and miR-184 in the pancreatic islets were suggested to be induced by hyperglycaemic and hyperlipidaemic conditions typically encountered in prediabetic and diabetic states37.…”
Section: Discussionmentioning
confidence: 69%
“…The inductions of miR-132 and miR-212 by GLP-1 were correlated with cyclic adenosine monophosphate (cAMP) production and were blocked by a protein kinase A inhibitor[17]. Overexpression of miRNA-132 or miRNA-212 increased glucose-stimulated insulin secretion [17]. We therefore hypothesized that miRNAs might be important in liraglutide-induced β-cell protection against lipid stress.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that several of the miRNAs showing altered expression in the GK rat are glucose-dependent (27), and we and others have shown cAMP-dependent regulation of miRNAs (28 -30). Specifically, the miR-212/miR-132 cluster has been suggested to be regulated by cAMP through a PKA-dependent mechanism (30) involving cAMP-response element (CRE)-binding proteins and CRTC1 (31).…”
Section: Camtasmentioning
confidence: 99%